Media Pendidikan Karakter Pada Pembelajaran Seni Karawitan di Kerobokan - Diantara, I Putu Arya; Trisnawati, Ida Ayu; Arshiniwati, Ni Made (STKIP AGAMA HINDU SINGARAJA, 2024)
This research aims to discuss the importance of character education for Sekehe Gong Taman Satya Budaya Kerobokan Kelod through the media of Gong Kebyar gamelan training. The data collection methods used were observation, literature study, documentation study and interviews where data collection was carried out by observation and interviews in the field. The analysis used is qualitative analysis. This research uses factors that influence the level of success in character education and is linked to the Gong Kebyar gamelan learning method. This is very significant considering that character education is an effort to embody the Sekehe Gong Taman Satya Budaya Kerobokan Kelod which is based on the reality of the problems in this research such as the decline in the quality of youth's attractiveness in participating in musical arts due to digital technology. By optimizing character education for youth at Sekehe Gong Taman Satya Budaya Kerobokan Kelod through the application of musical art teaching methods, especially Gong Kebyar, youth are expected to be able to increase good knowledge (moral knowing), good feelings (moral feeling) and good behavior (moral action). Theoretically, the results of this research are expected to contribute to the community of Banjar Taman Kerobokan Kelod so that it can help in increasing the intelligence of students and can be applied in both formal and informal learning processes, so that the aim of character education through art can provide material to students, so that they can also realize it significantly.